2019
DOI: 10.1111/aos.14120
|View full text |Cite
|
Sign up to set email alerts
|

Relating glaucomatous visual field loss to retinal oxygen delivery and metabolism

Abstract: Purpose To test the hypothesis that visual field (VF) loss is associated with decreased retinal blood flow, oxygen delivery and metabolism, and with increased retinal oxygen extraction fraction (OEF) in glaucomatous individuals. Methods Glaucomatous subjects underwent automated perimetry, dual wavelength scanning laser ophthalmoscopy and Doppler optical coherence tomography imaging in order to measure mean deviation, central retinal arterial and venous diameter equivalents (CRAE and CRVE), oxygen saturation le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
3
5
0
Order By: Relevance
“…In addition, Le et al50 reported an association between VF loss and peripapillary NFL thickness. The current study also showed a marginal correlation between decreased VF MD and decreased TRBF, consistent with findings reported by previous studies 9,23…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, Le et al50 reported an association between VF loss and peripapillary NFL thickness. The current study also showed a marginal correlation between decreased VF MD and decreased TRBF, consistent with findings reported by previous studies 9,23…”
Section: Discussionsupporting
confidence: 93%
“…Three MAP measurements were averaged per subject. Ocular perfusion pressure (OPP) was calculated as the difference between 2/3 MAP and IOP, as reported by previous studies 23,25…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study shows that retinal oxygen extraction is reduced in patients with glaucoma and is strongly correlated to the associated structural and functional damage. This is in keeping with a previous smaller-scale study in glaucoma patients [ 21 ]. Whereas several previous studies have shown that there is an association between ONH and/or retinal blood flow with glaucoma damage [ 22 , 23 , 24 , 25 , 26 , 27 ], our study links RGC damage to oxygen metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…Retinal vessel oxygen saturation is an emerging biomarker with potential in risk stratification of diabetic retinopathy (DR) [1] and linking structural and functional damage in ocular disease [2,3]. Numerous studies have shown that retinal venous oxygen saturation is increased in DR [4] and is linked with its severity [5].…”
Section: Introductionmentioning
confidence: 99%